THE DILEMMA OF ONLINE LEARNING DURING THE COVID-19: CHALLENGES OR OPPORTUNITIES? - Ira Irzawati (Universitas PGRI Palembang, 2021)
This research aimed to investigate the chalenges and opportunities of online learning system implementation from students' perspectives. In this survey research, 143 students of a private university were involved as the respondents. The respondents were third, fifth, and seventh-semester students from four different departments that have experienced learning English through an online learning system. The data of the research were gathered through administering an online survey to the respondents. The survey questionnaire covered items related to demographic information, online learning application, and chalenges and opportunities of online learning. The data of the survey were analyzed by presenting the frequency of students' responses towards each item of the questionnaire in form of a percentage. The students believed that online learning potentialy provided both chalenges and opportunities to the students. Technical issues, minimum interaction, low discipline, and a less effective learning atmosphere were among the dominant chalenges of online learning. Meanwhile, various material access, flexibility, interactive learning, and a relaxing learning atmo sphere were the major opportunities of online learning. Anticipating the chalenges and maximizing the opportunities are alternative solutions to promote the successful implementation of online learning.